Force-time curve variables of countermovement jump as predictors of volleyball spike jump height - Sarvestan, J.; Svoboda, Z.; Gustavo de Oliveira Claudino, J. (German Journal of Exercise and Sport Research, 2020)
Force-time (F-T) characteristics of countermovement jump (CMJ) are globally referenced as the main descriptors of athletic jump performance, particularly for volleyball players. Nevertheless, it is still unclear to what extent the vertical jump performance during testing is associated with jump performance during game-like conditions. This study was designed to investigate the association between F-T curve variables derived from CMJ, including movement timings, force, velocity, power, rate of force development (RFD), modified reactive strength index (RSImod), and net impulse with spike jump height during game-like circumstances. Thirteen young elite volleyball players performed three CMJs and six spike jumps in game-like circumstances. Pearson`s product correlation test portrayed a significant correlation between spike jump height and peak RFD (r= 0.75), average RFD (r= 0.76), RSImod (r= 0.56), and concentric net impulse (r= 0.61). Multiple regression analysis also showed that these factors have a strong contribution for predicting spike jump heights (71%). The findings of this study emphasise the importance of RFD, concentric net impulse, and RSImod values in the precise analysis and prediction of volleyball attackers` spike jump height during game-like conditions.